Ilmu Pendidikan Islam: Pengembangan Pendidikan Integratif di Sekolah, keluarga, dan Masyarakat - Roqib, Moh (LKiS Yogyakarta, 2009)
Ilmu Pendidikan Islam: Pengembangan Pendidikan Integratif di Sekolah, keluarga, dan Masyarakat